The Effect of Strategic Management and Human Capital Management on Teacher Performance in Several High Schools in Teluk Ambon District - Arnold Sahalessy; Donny Lessil (International Journal of Education, Information Technology, and Others, 2021)
This study aims to determine the effect of strategic management, human capital management on improving teacher performance in several high schools in Teluk Ambon District. The method used in this research is a survey method with a quantitative descriptive approach. In data collection, the instrument used was a Likert scale with a research scale of 1 to 5. The population in this study was 120 people, the research sample used a census sample or a total sample where all the population was sampled. To test the hypothesis using simple linear regression test statistics and multiple regression. The data analysis technique used is statistical descriptive analysis. In this study, technically analyzing all data using the computer program IBM SPSS (Statistical Packages For Social Sciences) version 26 for window 10, which is software to perform statistical analysis. Based on the results of the analysis, the researcher concludes that (1) there is a positive and significant effect of strategic management on teacher performance with Fcount of 3.209 and Ftable of 3.07 (Fcount>Ftable). These results were significant (p<0.05). (2) there is a positive and significant influence of human capital management on teacher performance with Fcount of 3.209 and Ftable of 3.07 (Fcount>Ftable). These results were significant (p<0.05). (3) there is a positive and significant effect of strategic management and human capital management together on teacher performance with Fcount of 227,789 and Ftable of 3.07 (Fcount>Ftable). These results are very significant (p<0.05).